Step
*
1
of Lemma
gen-continuity-contradicts-markov
1. ∀P:(ℕ ⟶ ℕ) ⟶ ℙ. ∀f:ℕ ⟶ ℕ.  ((P f) 
⇒ ⇃(∃k:ℕ. ∀g:ℕ ⟶ ℕ. ((f = g ∈ (ℕk ⟶ ℕ)) 
⇒ (P g))))
2. ∀A:ℕ ⟶ ℙ. ((∀n:ℕ. ((A n) ∨ (¬(A n)))) 
⇒ (¬¬(∃n:ℕ. (A n))) 
⇒ (∃n:ℕ. (A n)))
⊢ False
BY
{ Assert ⌜∀a:{a:ℕ ⟶ ℕ| init0(a) ∧ increasing-sequence(a)} . ∀m:ℕ.  ∃n:ℕ. ((a n) ≥ m )⌝⋅ }
1
.....assertion..... 
1. ∀P:(ℕ ⟶ ℕ) ⟶ ℙ. ∀f:ℕ ⟶ ℕ.  ((P f) 
⇒ ⇃(∃k:ℕ. ∀g:ℕ ⟶ ℕ. ((f = g ∈ (ℕk ⟶ ℕ)) 
⇒ (P g))))
2. ∀A:ℕ ⟶ ℙ. ((∀n:ℕ. ((A n) ∨ (¬(A n)))) 
⇒ (¬¬(∃n:ℕ. (A n))) 
⇒ (∃n:ℕ. (A n)))
⊢ ∀a:{a:ℕ ⟶ ℕ| init0(a) ∧ increasing-sequence(a)} . ∀m:ℕ.  ∃n:ℕ. ((a n) ≥ m )
2
1. ∀P:(ℕ ⟶ ℕ) ⟶ ℙ. ∀f:ℕ ⟶ ℕ.  ((P f) 
⇒ ⇃(∃k:ℕ. ∀g:ℕ ⟶ ℕ. ((f = g ∈ (ℕk ⟶ ℕ)) 
⇒ (P g))))
2. ∀A:ℕ ⟶ ℙ. ((∀n:ℕ. ((A n) ∨ (¬(A n)))) 
⇒ (¬¬(∃n:ℕ. (A n))) 
⇒ (∃n:ℕ. (A n)))
3. ∀a:{a:ℕ ⟶ ℕ| init0(a) ∧ increasing-sequence(a)} . ∀m:ℕ.  ∃n:ℕ. ((a n) ≥ m )
⊢ False
Latex:
Latex:
1.  \mforall{}P:(\mBbbN{}  {}\mrightarrow{}  \mBbbN{})  {}\mrightarrow{}  \mBbbP{}.  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.    ((P  f)  {}\mRightarrow{}  \00D9(\mexists{}k:\mBbbN{}.  \mforall{}g:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}.  ((f  =  g)  {}\mRightarrow{}  (P  g))))
2.  \mforall{}A:\mBbbN{}  {}\mrightarrow{}  \mBbbP{}.  ((\mforall{}n:\mBbbN{}.  ((A  n)  \mvee{}  (\mneg{}(A  n))))  {}\mRightarrow{}  (\mneg{}\mneg{}(\mexists{}n:\mBbbN{}.  (A  n)))  {}\mRightarrow{}  (\mexists{}n:\mBbbN{}.  (A  n)))
\mvdash{}  False
By
Latex:
Assert  \mkleeneopen{}\mforall{}a:\{a:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}|  init0(a)  \mwedge{}  increasing-sequence(a)\}  .  \mforall{}m:\mBbbN{}.    \mexists{}n:\mBbbN{}.  ((a  n)  \mgeq{}  m  )\mkleeneclose{}\mcdot{}
Home
Index